Integration of other services with human papillomavirus vaccination; lessons from earlier in the life course highlight the need for new policy and implementation evidence. (31st March 2022) - Morgan, Christopher; Giattas, Mary Rose; Holroyd, Taylor; Pfitzer, Anne; Engel, Danielle; Sidibe, Anissa; Holloway, Megan; Bloem, Paul; Fields, Rebecca; Shimp, Lora; Kumar, Somesh
Abstract: Integration of vaccination against human papillomavirus (HPV) with other essential health services for adolescents has been proposed in global strategies and tested in demonstration projects in low- and middle-income countries (LMIC). Published experiences, global guidance, and one key example, the implementation of "HPV Plus" in Tanzania, all demonstrate the need for greater operational evidence to guide future implementation and policy. Review of experiences earlier in the life course, integrating post-partum family planning with infant immunization, show lessons from 13 LMICs that can apply to provision of adolescent health information and services alongside HPV vaccination. Three distinct models of integration emerge from this review comprising: 1) multiple tasks and functions by health staff providing vaccination and other care, or 2) secondary tasks added to the main function of vaccination, or 3) co-location of matched services provided by different staff. These models, with strengths and weaknesses demonstrated in family planning and immunization experiences, apply in different ways to the three main platforms used for HPV vaccination: school, facility or community. For HPV vaccination policy and programming, an initial need is to combine the existing evidence on vaccine service delivery – including coverage, efficiency, cost, and cost-effectiveness information – with what is known on how integration works in practice; the operational detail and models employed. This synthesis may enable assessment which models best suit the different service delivery platforms. An additional need is to link this with more tailored local assessments of the adolescent burden of disease and other determinants of their well-being to develop new thinking on what can and cannot be done to integrate other services alongside HPV vaccination. New approaches placing adolescents at the center are needed to design services tailored to their preferences and needs. The potential synergies with cervical cancer screening and treatment for older generations of women, also require further exploration. Coordinated action aligning HPV vaccination with broader adolescent health and wellbeing will generate social, economic and demographic benefits, which in themselves are sufficient justification to devote more attention to integrated approaches.